Charge and Sequence Effects on the Self-assembly and Subsequent Hydrogelation of Fmoc-Depsipeptides - Nguyen, Mary M. (2014)
Herein we report on the self-assembly of a family of Fmoc-depsipeptides into nanofibers and hydrogels. We show that fiber formation occurs in depsipeptide structures in which the fluorenyl group is closely associated and that side-chain charge and sequence affect the extent of self-assembly and subsequent gelation. Using fluorescence emission spectroscopy and circular dichroism, we show that self-assembly can be monitored and is observed in these slow-gelling systems prior to hydrogel formation. We also demonstrate that the ionic strength of salt-containing solutions affects the time at which self-assembly results in gelation of the bulk solution. From transmission electron microscopy, we report that morphological changes progress over time and are observed as micelles transitioning to fibers prior to the onset of gelation. Gelled depsipeptides degraded at a slower rate than non-gelled samples in the presence of salt, while hydrolysis in water of both gels and solution samples was minimal even after 14 days. Our work shows that while incorporating ester functionality within a peptide backbone reduces the number of hydrogen bonding sites available for forming and stabilizing supramolecular assemblies, the substitution does not prohibit self-assembly and subsequent gelation.